Cyanidin‐3‐galactoside from Aronia melanocarpa ameliorates silica‐induced pulmonary fibrosis by modulating the TGF‐β/mTOR and NRF2/HO‐1 pathways. Issue 8 (30th March 2022) - Cui, Yanmin; Zhao, Jin; Chen, Jing; Kong, Yanwen; Wang, Mingyue; Ma, Yan; Meng, Xianjun
Abstract: Cyanidin‐3‐galactoside (C3G), the most abundant anthocyanin in Aronia melanocarp a, has many beneficial health effects, such as antioxidation. C3G was extracted from A. melanocarpa and applied (100, 200, and 400 mg/kg body weight) to 50‐μl silica particles (SP) solution‐exposed mice to research its antifibrotic properties using histological analysis, hydroxyproline assay, quantitative real‐time polymerase chain reaction, and western blot analysis. The results showed that C3G treatment significantly ameliorated pulmonary fibrosis and cell infiltration into the lungs of mice. It also relieved SP‐induced epithelial–mesenchymal transition (EMT), 400 mg/kg C3G treatment increasing epithelial‐cadherin mRNA expression and decreasing α‐smooth muscle actin mRNA expression to the level of that in the control group. Western blot analysis showed that exposure to SP increased the production of transforming growth factor‐β1 (TGF‐β1) and phosphorylated mammalian target of rapamycin (mTOR) by 4.71‐ and 4.15‐fold, respectively, in the lungs of mice, which were significantly inhibited by C3G treatment. Moreover, 400 mg/kg C3G treatment up‐regulated two important antioxidant mediators, nuclear factor erythroid‐2‐related factor 2 (NRF2; 4.91‐fold) and heme oxygenase‐1 (HO‐1; 4.81‐fold). The mechanism study indicated that C3G might inhibit the TGF‐β/mTOR signaling via the NRF2/HO‐1 pathway and that SP‐induced pulmonary EMT was ameliorated by inhibiting the TGF‐β/mTOR signaling pathway. Our findings could provide new avenues for C3G as a functional food for preventing or mediating the progression of SP‐induced pulmonary fibrosis. Abstract : Cyanidin‐3‐galactoside (C3G), the most abundant anthocyanin in Aronia melanocarpa, has many beneficial health effects, such as antioxidation. The mechanism study indicated that C3G might inhibit the transforming growth factor‐β (TGF‐β)/mammalian target of rapamycin (mTOR) signaling via the nuclear factor erythroid‐2‐related factor 2 (NRF2)/heme oxygenase‐1 (HO‐1) pathway and that silica particles (SP)‐induced pulmonary epithelial–mesenchymal transition (EMT) was ameliorated by inhibiting the TGF‐β/mTOR signaling pathway. The results indicate that C3G can be used as a complementary functional food to modulate pulmonary fibrosis caused by silica particles.